Survey of Verification as a Thai Nationality and Rights of Legal Person in RongKho, Sub-district Wang Nuea District Lampang Province - Sodamark, Keaitsuda; Maeban, Akkajohn (Rajapark Journal, 2022)
The objective of the study was to find out the problems with the verification of personal legal status and rights in Rong Kho Sub-district, Wang Nuea District, Lampang Province. This qualitative study used the data from documents, research, and fieldwork from an in-depth interview specifically with people whose statuses and rights were not legally verified in order to analyze the verification problems. The study results were as follows: 1. The problems Personnel Juridical Status Proving in Rong Kho Sub-district, Wang Nuea District, Lampang Province: the ethnic people migrating from Doi Luang National Park according to government policy, persons born in Thailand but classified as having no recognized status under the Thai Civil Registration Act and not recognized as Thai citizens under the Nationality Act. 2. The problems proof rights Attestation of the status of legal persons in Rong Kho Sub-district, Wang Nuea District, Lampang Province, involving an issue where some groups of people have proved their right to recognize the status of persons under the Civil Registration Act. The registrar creates a historical registry for people who do not qualify for registration. However, not everyone can provide proof that they are recognized under the Nationality Act.